2016
DOI: 10.1016/j.combustflame.2015.10.022
|View full text |Cite
|
Sign up to set email alerts
|

Understanding overpressure in the FAA aerosol can test by C3H2F3Br (2-BTP)

Abstract: Thermodynamic equilibrium calculations, as well as perfectly-stirred reactor (PSR) simulations with detailed reaction kinetics, are performed for a potential halon replacement, C3H2F3Br (2-BTP, C3H2F3Br, 2-Bromo-3,3,3-trifluoropropene), to understand the reasons for the unexpected enhanced combustion rather than suppression in a mandated FAA test. The high pressure rise with added agent is shown to depend on the amount of agent, and is well-predicted by an equilibrium model corresponding to stoichiometric reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…A great amount of studies have been focused on the inhibition chemistry mechanism, minimum extinguishing concentration, and combustion enhancement/suppression of 2-BTP by using theoretical calculation, model simulation or experiment [5,6,7,8,9,10,11,12,13,14,15,16,17]. According to previous studies, 2-BTP was considered to have a similar suppression performance to CF 3 Br given that both molecules contain a bromine atom and a CF 3 group [7,11]. Unfortunately, 2-BTP failed in the mandated FAA aerosol can test (FAA-ACT), like other potential replacements, i.e., C 2 HF 5 (HFC-125) and C 6 F 12 O (Novec 1230) [7,11,18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A great amount of studies have been focused on the inhibition chemistry mechanism, minimum extinguishing concentration, and combustion enhancement/suppression of 2-BTP by using theoretical calculation, model simulation or experiment [5,6,7,8,9,10,11,12,13,14,15,16,17]. According to previous studies, 2-BTP was considered to have a similar suppression performance to CF 3 Br given that both molecules contain a bromine atom and a CF 3 group [7,11]. Unfortunately, 2-BTP failed in the mandated FAA aerosol can test (FAA-ACT), like other potential replacements, i.e., C 2 HF 5 (HFC-125) and C 6 F 12 O (Novec 1230) [7,11,18].…”
Section: Introductionmentioning
confidence: 99%
“…According to previous studies, 2-BTP was considered to have a similar suppression performance to CF 3 Br given that both molecules contain a bromine atom and a CF 3 group [7,11]. Unfortunately, 2-BTP failed in the mandated FAA aerosol can test (FAA-ACT), like other potential replacements, i.e., C 2 HF 5 (HFC-125) and C 6 F 12 O (Novec 1230) [7,11,18]. In order to better understand why it promoted a higher overpressure when added at sub-inerting concentration and then reduced during the test, Babushok and Burgess et al developed a chemical kinetic mechanism to describe the flame inhibition chemistry of 2-BTP [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon might also explain overpressure increase observed in the FAA-ACT experiments [18] where the introduction of inhibition powders actually led to faster flames and higher overpressures. Many authors [38][39][40][41] have proposed an explanation for the observed overpressure increase based on thermodynamic equilibrium calculations and perfectly stirred reactor simulations. A non-uniform inhibitor distribution prior to ignition, and the subsequent flame surface increase, may also explain the increase in pressure during these experiments.…”
Section: Resultsmentioning
confidence: 99%
“…There are kinetic limitations when using the equilibrium simulations to predict the explosive pressure in FAA-ACT test. However, PSR simulations cannot only understand kinetic limitations [6] but also evaluate inhibition effectiveness of different agents through overall reaction rate during blow-out [15]. The PSR model is a classical idealization of the combustion process in which both physical and chemical mechanisms of fire suppression can be considered.…”
Section: Psr Modelmentioning
confidence: 99%
“…Babushok et al studied the combustion properties of halogenated fire suppressants [5] and calculated that approximate peak burning velocities of the pure 2-BTP-air flames were 1.15 cm/s, 2.15 cm/s, and 3.5 cm/s for initial mixture temperatures of 300 K, 400 K, and 500 K, respectively [1]. Afterwards, Linteris et al found when compressively preheated, 2-BTP/air mixture can support low-strain flames which are much more difficult to extinguish [6]. Pagliaro et al measured the laminar burning velocity of 2-BTP experimentally.…”
Section: Introductionmentioning
confidence: 99%